An efficient local search heuristics for asynchronous multiuser detection - Lim, Heng Siong; Venkatesh, B. (IEEE Xplore, 2003)
This letter considers the application of k-opt local search to the detection of data transmitted through the additive white Gaussian noise channel by K asynchronous users using direct-sequence code-division multiple access. The algorithm is based on a general approach to heuristics that is highly efficient in solving large combinatorial optimization problems. It is shown that the algorithm manage to produce optimum solutions with high frequency, in running time that grows about O(n(2)).